Effect of selenium enrichment on metabolism of tomato (Solanum lycopersicum) fruit during post‐harvest ripening - Puccinelli, Martina; Malorgio, Fernando; Terry, Leon A.; Tosetti, Roberta; Rosellini, Irene; Pezzarossa, Beatrice (Wiley, 2018)
BACKGROUND Selenium (Se) enrichment of plants seems effective in enhancing the health‐related properties of produce, and in delaying plant senescence and fruit ripening. The current study investigated the effects of Se on tomato fruit ripening. Tomato (Solanum lycopersicum L.) plants were grown in hydroponics with different Se‐enriched nutrient solutions. Se, as sodium selenate, was added at rate of 0 mg L‐1 (control), 1 mg L‐1, and 1.5 mg L‐1. RESULTS Selenium was absorbed by roots and translocated to leaves and fruit. Se enrichment did not significantly affect the qualitative parameters of fruit at commercial harvest, instead it delayed ripening by affecting specific ripening‐related processes (respiration, ethylene production, color evolution) during postharvest. In the current experiment 100 g of tomato hydroponically grown with a 1.5 mg Se L‐1 enriched solution provided a total of 23.7 μg Se. Selenium recommended daily intake is 60 μg for women and 70 μg for men, thus the daily consumption of 100 g of enriched tomato would not lead to Se toxicity, but would provide a good Se diet supplementation. CONCLUSIONS The cultivation of tomato plants in a Se‐enriched solution appeared effective in producing tomato fruit with improved performances during storage and postharvest shelf life, and also with greater potential health‐promoting properties.
Keywords: hydroponics; Se‐enriched fruit; storage; shelf‐life